Hemodynamic changes and quality of life in patients with prostate cancer after a HIIT and MICT training. A randomized clinical trial (ONCO-EXE TRIAL) - Pereira-Rodríguez, Javier Eliecer (2019)
Introduction. Prostate cancer is the most common in men and is the second cause of death. Exercise-based rehabilitation is effective and safe in mitigating cancer effects. Objective. To determine the hemodynamic changes and quality of life in prostate cancer after a high intensity training (HIIT) or continuous to moderate intensity (MICT). Methods. A randomized clinical trial with 249 patients with stage II prostate cancer divided into 3 groups (MICT, HIIT and control group) who were applied EORTC QLQ C-30 questionnaire for quality of life, echocardiogram, stress test, vital signs and FACT-Fatigue Scale. The training program lasted 36 sessions of 70 minutes, 3 times a week. Results. When comparing the post-training results of the hemodynamic variables, we managed to determine changes in the ejection fraction (GE1: 49.0 ± 5.6 vs 52.0 ± 5.4, GE2: 45.0 ± 5.3 vs 51.0 ± 3.2, GC: 48.0 ± 4.1 vs 48.0 ± 4.4 p<0.005), maximum heart rate (GE1: 155.0 ± 7.0 vs 159.0 ± 4.0, GE2: 156.0 ± 14.0 vs 168.0 ± 5.0, GC: 155.0 ± 7.0 vs 155 ± 6.0, p<0.005). As in the results for quality of life (GE1: 55.1 ± 10.3 vs 70.9 ± 10.2, GE2: 59.8 ± 9.9 vs 118.0 ± 14.6, GC: 60.2 ± 7.6 vs 62.3 ± 9.4, p<0.005). Conclusions. HIIT and MICT significantly improved the quality of life, fatigue, and all hemodynamic variables evaluated in the research. Greater benefits were demonstrated with HIIT. The usual care control group without physical training did not show significant changes.